Green Synthesis Of Antibacterial Silver Nanoparticles Using Grewia Asiatica Leaf Extract: Characterization And Potential For Combatting Antibiotic-Resistant Bacteria - Ahmad, Abbas; Muhammad, Javeed; Dinislam, Khuzin; Maria, Makarevich; Elizaveta, Voskresenskaya; Madina, Dzhukkayeva; Alexey, Orlov; Khadizhat, Aydekova; Polina, Strok; Ekaterina, Oshurkova; Victoria, Pimenova (Migration Letters, 2024)
Background: Grewia asiatica Linn. is a shrub or small tree with a fruit of 5–12 mm diameter, having a purple to black color when it is ripe. The current global rise in antibiotic-resistant bacteria, associated with a steady decline in the development of new antibiotics has serious repercussions. Objective: The study aimed to develop and establish a safe, eco-friendly, cheaper method for the synthesis of silver nanoparticles using leaf extract of Grewia asiatica. Methods: The AgNPs were characterized using standard techniques, and their antimicrobial activity was evaluated against Acinetobacter baumannii and Salmonella enterica serovar Typhi to determine minimum inhibitory concentration. Results: The silver nanoparticles exhibit significant antibacterial activity against Acinetobacter baumannii and Salmonella typhi, their zone of inhibition was 8.43±1.53 nm and 8.34±1.73 nm, respectively. The XRD result revealed that the strongest reflection at 38.13º is the crystalline nature and face-centered-cubic structure of synthesized Ag-NPs. The green synthesis of three different AgNPs in different concentrations according to 0.1 molar, 0.01, and 1 molar solution was obtained to be 96 nm, 110nm, and 91nm in size respectively All samples have a low polydispersity index (PDI) of 0.46, 054, and 0.35, and their Zeta potential value was 23.7mv. FTIR spectrum result showed the presence of alkenes, Aromatic ketone, and alkyl halides which help in the reduction of silver ions to silver nanoparticles. The morphology of biosynthesized silver NPs further analyzed by scanning SEM the average size of AgNPs was found to be in the array of 40 nm to 80 nm. The analysis of optical properties of nanomaterials through Ultraviolet photo[1] spectrometry range between 200nm to 800nm revealed that AgNPs synthesized nanomaterial was seeing a peak of 477nm. Silver nanoparticles and leaf extract were tested against two-gram negative bacteria Acinetobacter baumannii and Salmonella typhi. AgNPs and G. asiatica extract indicate that Salmonella typhi is more sensitive to AgNPs and G. asiatica extract as compared to Acinetobacter baumannii. Conclusion: This study concludes that the green synthesis of silver nanoparticles by using Grewia asiatica plant extract is possible and these silver nanoparticles have potent antibacterial activity and can be used as an alternative to antibiotics. So, these nanoparticles can be used against multi-drug-resistant bacterial infections.